2012
DOI: 10.1007/s12311-012-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar Ataxia Type 7: Clinical Course, Phenotype–Genotype Correlations, and Neuropathology

Abstract: INTRODUCTION Spinocerebellar ataxia type 7 is a neurodegenerative polyglutamine disease characterized by ataxia and retinal degeneration. The longitudinal course is unknown, and relationships between repeat expansion, clinical manifestations, and neuropathology remain uncertain. METHODS We followed 16 affected individuals of a 61-member kindred over 27 years with electroretinograms, neurological examinations including the Brief Ataxia Rating Scale, neuroimaging in 5, and autopsy in 4 cases. RESULTS We iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 32 publications
10
79
0
Order By: Relevance
“…The gene causing SCA7 is located on chromosome 3p21-p12 and encodes for a protein named ataxin-7. Although ataxin-7 is broadly expressed, the pathology is primarily localized in the cerebellum and retina [14]. It has been reported that neuropathological hallmarks of SCA7 include neuronal loss in the cerebellar cortex, deep cerebellar nuclei, inferior olive, and anterior horns of the spinal cord, as well as axonal loss in spinocerebellar tracts [14].…”
Section: Introductionmentioning
confidence: 99%
“…The gene causing SCA7 is located on chromosome 3p21-p12 and encodes for a protein named ataxin-7. Although ataxin-7 is broadly expressed, the pathology is primarily localized in the cerebellum and retina [14]. It has been reported that neuropathological hallmarks of SCA7 include neuronal loss in the cerebellar cortex, deep cerebellar nuclei, inferior olive, and anterior horns of the spinal cord, as well as axonal loss in spinocerebellar tracts [14].…”
Section: Introductionmentioning
confidence: 99%
“…SCA7 accounts for approximately 2 to 5 percent of all SCA and has a variable clinical expression, particularly depending on age at onset and CAG repeat 7 . Thus, the higher the number of repetitions, the more severe the disease, and the earlier the onset of symptoms 7 . Extremely long CAG repeats (.…”
Section: Discussionmentioning
confidence: 99%
“…Normal alleles contain 4-35 CAG repeats, whereas pathological alleles for SCA7 contain from 36-306 CAG repeats 7 . Besides cerebellar signs, the main neurological manifestations of SCA7 include visual loss, due to macular changes, cone dysfunction, retinal pigmentary dystrophy and ophthalmoplegia 8,9,10 .…”
mentioning
confidence: 99%
“…The gene has 13 exons with the polyQ repeat region in exon 3, the first coding exon of the gene. The healthy repeat range in SCA7 is 7-19, with an incomplete penetrance of 19-35, while a wide disease range of 36 to >400 repeats has been reported ( Table 2) [172]. Although all SCA diseases have a tendency for genetic anticipation, ATXN7 is particularly known to be highly unstable, resulting in extreme anticipation and expansion during paternal transmission [38].…”
Section: Molecular Geneticsmentioning
confidence: 99%